Exploring resilience capacities with food innovators: a narrative approach - Megan Lindow; Rika Preiser; Reinette Biggs (Global Sustainability, 2020)
We interviewed grassroots food innovators in South Africa to explore the diverse ways in which their narratives expressed different capacities for resilience, such as dealing with surprise and shaping desirable change. We drew on key resilience themes of rootedness, resourcefulness and resistance (the 3Rs) as lenses through which to view their personal stories and efforts to build resilience and reshape the future. We used narrative and interpretative methods to connect the personal and context-specific experiences of food innovators to the 3Rs, exploring a new approach to uncovering resilience capacities. We suggest that this approach could be usefully employed to understand potential resilience capacities that could help address diverse sustainability challenges around the world.